Access to algorithms post-Robodebt: Do Freedom of Information laws extend to automated systems?. (March 2022) - Ray, Andrew; Adams, Bridie; Thampapillai, Dilan
This article analyses how current Freedom of Information (FOI) laws apply to automated decision-making systems. The authors argue that while current law may extend to automated systems, its application is unclear, both to practitioners and government. Instead, amendments to the FOI Act 1982 (Cth) could clarify how the law operates with respect to automated systems and better balance the underpinning objectives of the Act.